Challenges and difficulties in memorizing the Qurʾan in the tahfiz classes among secondary learners - Nik Abdullah, Nik Md. Saiful Azizi; Mohd Sabbri, Fathiyah Solehah; Muhammad Isa, Rabi'atul Athirah (IIUM Press, International Islamic University Malaysia, 2019)
The current trend shows that most parents are interested in making sure that their children received the tahfiz and Quran education. However, no matter how good the Tahfiz programs are, they are not complete without relating it to motivation. Hence, this study was conducted to explore the motivation behind the children’s memorization of the Qurʾan and the challenges and obstacles faced by them in fulfilling the task. This article explores the challenges faced by students in Qur’an memorization in the Tahfiz class setting through a qualitative study of semi-structured interviews via one-on-one interaction by exploring the challenges and difficulties in memorizing the Qur’an. In particular, the researchers used open-ended interview structure which included specific questions, followed up by probing questions to investigate the phenomenon in details. Participants in this study were made up of 6 Tahfiz students (3 females and 3 males), whose ages ranged between 15 to 17-year olds, exploring the techniques used by students in Quranic memorization in the Tahfiz class. The findings suggested that the feeling of empathy, parents’ prayer and advice, continuous repetitions, early morning practices, smart scheduling for memorizing, having a partner to memorize, introspection, punishment and other learning materials helps in overcoming the barriers in Quranic memorization